Life in Patipatti Monasteries - Visuta, Ven. (Journal of Dhamma for Life, 2021)
The article aim to present on the topic names “Life in Patipatti Monasteries”. Besides Pariyatti monasteries, there are a number of Patipatti monasteries in every town and city. They take the responsibility of Vipassanædhura that is teaching meditation to both monks and laypeople. Some famous meditation centres in Myanmar include Mahasi Meditation Centre, Moghok Meditation Centre, Pa-auk Meditation Centre, Ledi Meditation Centre, Dhammadūta Meditation Centre, Vebhu Meditation Centre, and Set Yon Meditation Center. Each of them has branches in villages and cities throughout Myanmar. They offer seemingly different techniques, but in essence, they all teach the methods as taught by the Buddha. The differences are only due to the approach to those methods. Although meditation is basically of two kinds – Samatha (concentration meditation) and Vipassanā (insight meditation), all the meditation centres offer Vipassanā meditation except the fact that some of them start with Samatha before the students are taught to practice Vipassanā.